Biological role of the soluble interleukin-2 receptor in sarcoidosis - Vanmaris, Remi M; Rijkers, Ger T (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Sarcoidosis is a systemic inflammatory disease characterized by granulomatous inflammation. The soluble interleukin-2 receptor (sIL-2R) is used as a biomarker for disease severity in sarcoidosis. Moreover, rather than just a biomarker, evidence indicates that sIL-2R could be of biological significance in this disease. The aim of this review is to investigate both its qualities as a biomarker and a potential biological role in sarcoidosis. As a biomarker, the serum level of sIL-2R can be used to distinguish patients from healthy controls, active from inactive disease and to assess treatment success. Additionally, sIL-2R correlates with other biomarkers, including angiotensin-converting enzyme, and with lung function tests and nuclear imaging studies. In sarcoidosis T helper cells and alveolar macrophages are the most likely sources of sIL-2R. While most of the evidence indicates that sIL-2R is generated through proteolytic cleavage of membrane-bound IL-2Ra, no endogenous enzyme has been found to be clearly responsible for sIL-2R formation. It is unclear if sIL-2R has immunostimulatory, immunomodulatory or no functional effects, since conflicting results have been reported. Several potential mechanisms of sIL-2R’s biological functions include IL-2 sequestration, prolonging IL-2 half-life, preventing activation of resting T cells or increasing affinity of IL-2Rb for IL-2. The most likely function of sIL-2R is to modify IL-2 signaling. Increased levels of sIL-2R could either promote disease processes, represent an ineffective attempt to resolve the inflammation or have no effect at all. Further research is required to determine its exact role in the disease and thus its usefulness as a therapeutic target.